Non-thermal electrons in an eruptive solar event: Magnetic structure, confinement, and escape into the heliosphere - Klein, Karl Ludwig (2024)
Context. Filament eruptions and coronal mass ejections (CMEs) reveal large-scale instabilities of magnetic structures in the solar corona. Some of them are accompanied by radio emission, which at decimetric and longer wavelengths is a signature of electron acceleration that may be different from the acceleration in impulsive flares. The radio emission is part of the broadband continua at decimetre and metre wavelengths called type IV bursts. Aims. In this article we investigate a particularly well-observed combination of a filament eruption seen in Hα and at extreme ultraviolet (EUV) wavelengths and a moving type IV burst on 2021 August 24. The aim is to shed light on the relationship between the large-scale erupting magnetic structure and the acceleration and transport of non-thermal electrons. Methods. We used imaging observations of a moving radio source and associated burst groups with the refurbished Nançay Radioheliograph and whole-Sun radio spectrography from different ground-based and space-borne instruments, in combination with X-ray, radio, and in situ electron observations at tens of keV from Solar Orbiter and EUV imaging by SDO/AIA. The radio sources are located with respect to the erupting magnetic structure traced by the filament (EUV 30.4 nm), and the timing of the electrons detected in situ is compared with the timing of the different radio emissions. Results. We find that the moving radio source is located at the top of the erupting magnetic structure outlined by the filament, which we interpret as a magnetic flux rope. The flux rope erupts in a strongly non-radial direction, guided by the overlying magnetic field of a coronal hole. The electrons detected at Solar Orbiter are found to be released mainly in two episodes, 10–40 minutes after the impulsive phase. The releases coincide with two groups of radio bursts, which originate respectively on the flank and near the top of the erupting flux rope. Conclusions. The observation allows an unusually clear association between a moving type IV radio burst, an erupting magnetic flux rope as core structure of a CME, and particle releases into the heliosphere. Non-thermal electrons are confined in the flux rope. Electrons escape to the heliosphere mainly in two distinct episodes, which we relate to magnetic reconnection between the flux rope and ambient open field lines.